Formaldehyde And Benzo(Î‘)Pyrene induced Cells Necrotic in Mice Liver - Soni, Ahmad; Widyarti, sri; Suwondo, Aris (Journal of Tropical Life Science, 2013)
Formaldehyde and benzo(α)pyrene are compounds that harmful for health. Misapplication of this compound have an impact in the form of organ damage in the body. This study aims to determine the impact of the treatment of the combined exposure of formaldehyde and benzo(α)pyrene to cell necrosis in the liver of mice (Mus musculus). Treatment of formaldehyde dose of 25 mg/kg BW to mice were given â€‹â€‹orally every day for 60 days. Treatment of benzo(α)pyrene via intraperitoneal injection at a dose of 250 mg/kg BW were given after 30 days of incubation with four times injection with one day interval. Liver organ histological preparations were made through the HE staining. Observations were made by using a microscope for liver organ preparations. The data obtained that is the percentage of cells necrosis and necrotic foci. This research used Completely Randomized Design (CRD) with 95% confidence interval. Liver organ preparations observations indicate that the percentage of necrosis in the untreated control, benzo(α)pyrene 250 mg/kg BW, Formaldehyde 25 mg/kg BW, combination of formaldehyde 25 mg/kg BW with BaP in a row that is equal to 14.43% ± 0.91; 26.05% ± 3.75; 49.38% ± 2.66; 51.86 ± 1.73. The mean of necrotic foci in liver organ formed in the untreatment control, benzo(α)pyrene 250 mg/kg BW, Formaldehyde 25 mg/kg BW, and the combination of formaldehyde 25 mg/kg BW with BaP in a row, equal to 1.3 ± 0,07; 1.63 ± 0.61; 2 ± 0.51, and 3.4 ± 0.76. This suggests that the combined treatment had the highest level of toxicity compared with other treatments.